The importance of green human capital in green logistic processes in Polish enterprises - Górska Monika; Prusak Rafał (2023)
Due to the high market dynamics, economic and environmental, constantly growing and changing customer needs, each organization is looking for new solutions related to the technology of goods flow, process optimization, aimed at both improving the quality of products and improving their production processes towards reducing their impact on the natural environment. In this context, Green Human Resources (GHR) may become a key factor in the success of greenlogistics (GL), because the success of the company depends in particular on the actions of employees, their knowledge, skills and their use and awareness. Therefore, the goalof the research was to check how the method of managing green human capital influences changes in the functioning of enterprises in selected areas related to the course and quality of logistics processes (including in terms of GL). As research shows, companies use GHR to promote behaviors among employees that increase the ecological efficiency of the entire company, but their share is still negligible. The study was conducted using an electronic survey questionnaire on a group of 200 enterprises. The conducted research showed the relationship between the importance of individual elements of human capital in enterprise strategies and changes in the functioning of enterprises in selected areas related to the course and quality of logistics processes. The following components had the greatest impact on the studied effects: human capital: knowledge, personal and social skills, interpersonal relations and psychological characteristics of employees.